The perfect state, the strong state and the deadlock of political Islam: the case of Turkey. Issue 2 (3rd July 2022) - Azeri, Siyaves
Abstract : Erdogan's 'moderate' political Islamist administration was initially introduced in Turkey as the bourgeois state that would facilitate the implementation of neo-liberal economic order and a new cycle of accumulation of capital. However, Erdogan's breed of Islamism has proven itself incapable of constituting the bourgeois 'strong state'. The inability of political Islam to constitute the 'strong state' is rooted in its tendency toward violating the separation of the state (political sphere) from the bourgeois (civil) society—the 'perfect state'. Political Islam, by definition, is contradictory and consequently is necessarily a source of crisis; its failure in constituting the strong state is inevitable because it necessarily violates the principles of the 'perfect state'—the precondition of the emergence of the 'strong state'— 'which relegates religion to a place among the other elements of civil society'.